Eco-Qurani for Children (Instilling Al-Qur'an Values about Environment to Children in Pegandon Karangdadap Village, Pekalongan) - Kurdi Fadal; Heriyanto Heriyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2018)
Pegandon Village, Karangdadap District, Pekalongan, one of the areas affected by the Pemalang-Batang toll road. The project has many negative impacts on the communities around the village, including children. This village is also known as a village with vast rice fields and rivers in the area. Children are the environmental assets of the future that play a very important role in preserving natural resources. So, their understanding of the Qur'anic teachings about environment is the key to maintaining human relations with nature. With a good understanding, it fosters the sensitivity to be a creature for nature in future generations. This empowerment is intended to provide understanding and sensitivity of children, especially for students of Quranic Education Park (TPQ) and Madrasah Diniyah Bustanul Iman, Pegandon Karangdadap Village, Pekalongan. Empowerment is built with the assistance method with a contextual, cooperative and problem-based approach. Empowerment is presented through the introduction of verses that teach about the environment, including natural wealth, the prohibition of damaging the environment and the obligation to preserve it. The series of activities that have been carried out have positive implications for children of TPQ and Madrasah Diniyah Bustanul Iman because they have been able to understand and practice environmental verses as teachings to preserve the environment from damage and efforts to conserve it.